Organoruthenium-catalyzed chemical protein synthesis to elucidate the functions of epigenetic modifications on heterochromatin factors. Issue 16 (29th March 2021) - Kamo, Naoki; Kujirai, Tomoya; Kurumizaka, Hitoshi; Murakami, Hiroshi; Hayashi, Gosuke; Okamoto, Akimitsu
Abstract : Chemical protein synthesis assisted by an organoruthenium catalyst streamlined the production of heterochromatin factors bearing various patterns of epigenetic modifications, and their biological significance was elucidated. Abstract : The application of organometallic compounds for protein science has received attention. Recently, total chemical protein synthesis using transition metal complexes has been developed to produce various proteins bearing site-specific posttranslational modifications (PTMs). However, in general, significant amounts of metal complexes were required to achieve chemical reactions of proteins bearing a large number of nucleophilic functional groups. Moreover, syntheses of medium-size proteins (>20 kDa) were plagued by time-consuming procedures due to cumbersome purification and isolation steps, which prevented access to variously decorated proteins. Here, we report a one-pot multiple peptide ligation strategy assisted by an air-tolerant organoruthenium catalyst that showed more than 50-fold activity over previous palladium complexes, leading to rapid and quantitative deprotection on a protein with a catalytic amount (20 mol%) of the metal complex even in the presence of excess thiol moieties. Utilizing the organoruthenium catalyst, heterochromatin factors above 20 kDa, such as linker histone H1.2 and heterochromatin protein 1α (HP1α), bearing site-specific PTMs including phosphorylation, ubiquitination, citrullination, and acetylation have been synthesized. The biochemical assays using synthetic proteins revealed that the citrullination at R53 in H1.2 resulted in the reduced electrostatic interaction with DNA and the reduced binding affinity to nucleosomes. Furthermore, we identified a key phosphorylation region in HP1α to control its DNA-binding ability. The ruthenium chemistry developed here will facilitate the preparation of a variety of biologically and medically significant proteins containing PTMs and non-natural amino acids.